Rancang Bangun Aplikasi Denah Kampus Politeknik Negeri Sambas Berbasis Web - Heldi, Heldi Hastriyandi; Wahyuni, Sri; Syahnaz, Erifa (Sehati Abdimas, 2024)
The rapid advancement of technology, particularly in the era of digitalization, demands the provision of information that is more efficient and easily accessible. Currently, information about campus maps and layouts is often presented in manual forms, such as layouts displayed in the campus Directorate in the form of showcases using miniatures, which appear less engaging and informative. However, the importance of conveying information related to campus maps, facilities, and routes between buildings is increasingly evident. This includes supporting facilities such as sports areas, religious spaces, gardens, cafes, laboratories, libraries, student dormitories, and practical learning facilities like gardens, greenhouses, and fish farming ponds. To address these challenges, a new breakthrough in delivering information about the campus map and its facilities is necessary. One effective solution is to digitize the campus map in the form of a web application. This way, the information can be easily accessed by anyone through devices connected to the internet. This web-based campus map application will facilitate students, especially newcomers, staff, and campus visitors in locating desired facilities, speeding up orientation within the campus environment, and enhancing the overall user experience. With this digitalization, it is hoped that the use of information technology in accessing campus information will provide a more interactive and informative experience for users, as well as facilitate both academic and non-academic activities at Politeknik Negeri Sambas more efficiently and effectively. This research is designed using the Waterfall method, which includes data analysis, database design, UML, and interface development. The system will be validated through testing and demonstration, meeting the Technology Readiness Level (TRL) 8.